Disparatis Kewenangan Badan Narkotika Nasional dan Penyidik Kepolisian dalam Penyidikan Tindak Pidana Narkotika - Pungky Dwiki Enriko; Wiwik Afifah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Crimes, wrongdoings, criminal crimes, and punishable actions are all colloquially known as unlawful acts. There has been a recent uptick in reports of drug misuse. This is supported by the many news articles published in newspapers and online that touch with the topic of drug misuse, including smuggling, illicit commerce, arrests, and detentions. Law no. 35 of 2009, the Narcotics Law, was ultimately passed by the government in response to the seriousness of the problem and the widespread availability of illicit drugs in Indonesia. The goal of this law is to curb the growing problem of drug abuse and distribution inside the country. Everybody is crossing their fingers that the new drug legislation will be effective and that the current penalties for drug offenses may be decided upon properly. A nation's existence, particularly that of its youth, is greatly affected by drugs, which is why narcotics laws must be strictly enforced.